Diversidade de populações de Phyllosticta spp. de goiabeiras e de mangueiras em diferentes ambientes - Carboni, Roberta Cristina Delphino [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Phyllosticta corresponds to an important genus of fungi associated with the plant kingdom. Due to the economic importance of damages caused by some species of Phyllosticta and the cosmopolitan behavior of endophytic species, several studies have been conducted in order to identify and reclassify species of this genus. Through the application of sequencing of different gene regions, new species of Phyllosticta were recently reported, and concomitant to the new reports, doubts were raised about the identification of previously reported and commonly cited species in literature. In this context, studies indicated that mango is hosted by different endophytic species of Phyllosticta spp. and that P. capitalensis can cause lesions on guava fruits, whose symptoms were previously attributed to other species of the genus. Thus, because of the reclassification and identification of new species, it was necessary to perform studies of the complex of Phyllosticta species not yet known, by continuing the work already carried out in Brazil with guava and mango crops in which the identification of the fungus is still unclear. Therefore, this study aimed to obtain a current collection of Phyllosticta isolates from asymptomatic leaves of guava and mango, and symptomatic fruits of guava. Leaves samples of both plant species were collected in germplasm banks and in areas of commercial production of the fruits. It were selected 102 isolates, according to their phenotypic characteristics in culture medium, to be submitted to the sequencing of ITS1-5.8S-ITS2, actin (ACT) and glyceraldehyde 3-phosphate dehydrogenase (GPDH) genes. Also, in order to corroborate the results obtained by sequencing and aiming to analyze the genetic profile of the isolates, fAFLP markers (fluorescent Amplified Fragment Length Polymorphism) analysis were applied. Both techniques allowed the separation of isolates according to their species, which were identified as ...

Phyllosticta corresponde a um importante gênero de fungos associados ao reino vegetal. Devido à importância econômica dos prejuízos ocasionados por algumas espécies de Phyllosticta e ao comportamento cosmopolita das espécies endofíticas, várias pesquisas têm sido realizadas no intuito de identificar e reclassificar as espécies desse gênero. Mediante a aplicação do sequenciamento de diferentes regiões gênicas, novas espécies de Phyllosticta foram relatadas recentemente, e concomitante aos novos relatos, surgiram dúvidas acerca da identificação das espécies já relatadas e comumente citadas na literatura. Neste contexto, estudos indicaram que mangueiras são hospedeiras de diferentes espécies endofíticas de Phyllosticta spp. e, que P. capitalensis pode ocasionar lesões em frutos de goiabeiras, cujos sintomas eram até então atribuídos à outra espécie do gênero. Assim, tendo em vista a reclassificação e identificação de novas espécies, fez-se necessário a realização de estudos do complexo de espécies de Phyllosticta ainda não conhecidas, dando continuidade aos trabalhos já realizados no Brasil em mangueiras e goiabeiras, culturas nas quais a identificação do fungo ainda não está bem esclarecida. Para tanto, este trabalho objetivou obter uma coleção atual de isolados de Phyllosticta de folhas assintomáticas de goiabeiras e de mangueiras, e de frutos sintomáticos de goiabeiras. Amostras de folhas de ambas as espécies de plantas foram coletadas em bancos de germoplasma e em áreas de produção comercial. Foram selecionados 102 isolados, segundo suas características fenotípicas em meio de cultura, para serem submetidos ao sequenciamento da região ITS1-5.8S-ITS2, e dos genes codificadores da actina (ACT) e do gliceraldeído-3-fosfato desidrogenase (GPDH). Ainda, a fim de corroborar os resultados obtidos pelo sequenciamento e objetivando analisar o perfil genético dos indivíduos, foram ...
Keywords: Goiaba; Manga (Fruta); Plantas - Nutrição; Fungos fitopatogenicos; Marcadores genéticos; Genetica vegetal; Genetic markers